Wound Infection after Laparoscopic-Assisted Gastrostomy in Infants - Burman, Linnéa; Diaz, Maia; Viktorsdóttir, Margrét Brands; Sjövie, Helen; Stenström, Pernilla; Salö, Martin; Arnbjörnsson, Einar Ólafur (The Surgery Journal, 2019)
Background Gastrostomy placement in children is one of the most frequently performed pediatric surgical procedures and laparoscopic-assisted gastrostomy (LAG) is the preferred technique. Wound infection after LAG has become a significant concern due to the emergence of antibiotic resistance. The aim of this study was to describe the frequency of wound infection after LAG in children younger than 2 years of age and to identify the associated risk factors and the bacterial species involved.Methods Information about wound infection, results from bacterial cultures, and type of antibiotic treatment used within 30 postoperative days after LAG were compiled for infants who underwent LAG from 2010 to 2017. A retrospective chart review was performed. Data was compiled from charts and from an electronic database containing prospectively collected data. A multivariate logistic analysis was used to explore potential risk factors. Preoperative antibiotic prophylaxis and postoperative local wound care were conducted according to standard procedures.Results The 141 included infants underwent surgery at a median age of 10 months (range: 1–24). Thirty-eight (27%) patients had a clinically determined wound infection, bacteria were cultured from 26/38 (69%), and 30/38 (79%) received antibiotic treatment. The median interval from surgery to detection of a clinical wound infection was 14 days (range: 4–30). The most common microbes discovered were skin bacteria Staphylococcus aureus or Streptococcus pyogenes, but respiratory and intestinal bacteria were also found. Multivariate logistic regression analysis revealed no independent risk factors for infection such as age, gender, or underlying diagnosis.Conclusion Infants have a high rate of postoperative clinical wound infection after LAG despite the use of preoperative antibiotic prophylaxis and intense local wound care. Gender, age at operation, and previous diagnoses were not found to be independent risk factors for wound infection.
Keywords: laparoscopic-assisted gastrostomy; infants; wound infections; complications; bacterial culture; antibiotics